Partial pressure (or fugacity) of carbon dioxide, salinity and other variables collected from Surface underway observations using Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and other instruments from Marcus G. Langseth in the Aegean Sea, Alboran Sea and others from 2015-04-13 to 2015-11-12 (NCEI Accession 0144534) ... - Takahashi, Taro; Sweeney, Colm; Sutherland, Stewart C. (NOAA National Centers for Environmental Information, 2016)
This dataset includes Surface underway data collected from Marcus G. Langseth in the Aegean Sea, Alboran Sea, Mediterranean Sea, Mediterranean Sea - Eastern Basin, Mediterranean Sea - Western Basin, North Atlantic Ocean and Strait of Gibraltar from 2015-04-13 to 2015-11-12. These data include BAROMETRIC PRESSURE, Partial pressure (or fugacity) of carbon dioxide - water, SALINITY and SEA SURFACE TEMPERATURE. The instruments used to collect these data include Carbon dioxide (CO2) gas analyzer and Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement. These data were collected by Stewart C. Sutherland and Taro Takahashi of Lamont-Doherty Earth Observatory (LDEO) and Colm Sweeney of NOAA Earth System Research Laboratory (ESRL) as part of the VOS_Marcus_Langseth_Lines_2015 dataset. CDIAC associated the following cruise ID(s) with this dataset: 33H320150413 ...